Evaluasi Pendidikan Inklusi Di Sekolah Dasar Kecamatan Koja Jakarta Utara - Fitriana Fitriana; Ika Lestari; Amalia Sapriati (Universitas Cokroaminoto Palopo, 2022)
The implementation of inclusive education aims to provide education for all, including children with special needs. The type of specialty that is most often encountered is slow learner. Adjustments need to be made by schools, both in terms of curriculum, educational facilities and infrastructure and learning systems. This is a separate obstacle in its implementation. The CIPP evaluation study used a descriptive qualitative method. Interviews, observations, questionnaires, and literature research became the research objects, and the research objects were principals and teachers. The results of the evaluation show that there is no element of inclusive education in school development plans and special budgets that have an impact on school management, without day-to-day financial or material assistance, without a curriculum tailored to the needs and development of students, and teachers ill-prepared to develop and implement plan Individual learning, school facilities and infrastructure that are not appropriate and the learning process is not in accordance with the accommodative curriculum.At the same time, the assessment criteria did not meet the minimum procedural standard criteria. Various aspects of the CIPP evaluation concluded that the readiness of schools to implement inclusive education still needs to be improved